First record of Lasiurus egregius (Peters, 1870) (Chiroptera, vespertilionidae) in Paraná state, Southern Brazil - Carvalho, Fernando (2019)
Lasiurus egregius (Peters, 1870) is an insectivorous bat species known from Central and South America. This species has few confirmed records throughout its distribution. Here we report the first record of L. egregius from the northern coast of Paraná state, southern Brazil. We captured a female individual of L. egregius using an ultrathin mist-net installed over a river knee, at Salto Morato Natural Reserve, municipality of Guaraqueçaba. This is the fourteenth locality with confirmed occurrence of L. egregius, being eight of them in Brazil. The knowledge on the bat fauna in Paraná has been increasing in recent decades, mainly due to the new studies in coast areas of this state. In addition to contributing to the knowledge of the bat fauna from Paraná, the new record of L. egregius reinforces the essential role of the Salto Morato Natural Reserve in conserving bats in the southern portion of the Atlantic Forest. © 2019, Pensoft Publishers. All rights reserved.